VLA and ALMA observations of the lensed radio-quiet quasar SDSS J0924+0219: a molecular structure in a 3 μJy radio source. Issue 1 (30th May 2020) - Badole, Shruti; Jackson, Neal; Hartley, Philippa; Sluse, Dominique; Stacey, Hannah; Vives-Arias, Héctor
ABSTRACT: We present Karl G. Jansky Very Large Array (VLA) and Atacama Large Millimetre Array (ALMA) observations of SDSS J0924+0219, a z = 1.524 radio-quiet lensed quasar with an intrinsic radio flux density of about 3 μ Jy. The four lensed images are clearly detected in the radio continuum and the CO(5–4) line, whose centroid is at z = 1.5254 ± 0.0001, with a marginal detection in the submillimetre continuum. The molecular gas displays ordered motion, in a structure approximately 1–2.5 kpc in physical extent, with typical velocities of 50–100 km s −1 . Our results are consistent with the radio emission being emitted from the same region, but not with a point source of radio emission. SDSS J0924+0219 shows an extreme anomaly in the flux ratios of the two merging images in the optical continuum and broad emission lines, suggesting the influence of microlensing by stars in the lensing galaxy. We find the flux ratio in the radio, submillimetre continuum and CO lines to be slightly greater than 1 but much less than that in the optical, which can be reproduced with a smooth galaxy mass model and an extended source. Our results, supported by a microlensing simulation, suggest that the most likely explanation for the optical flux anomaly is indeed microlensing.